Effects of Day-to-Day Affect Regulation on the Pain Experience of Patients with Rheumatoid Arthritis - Connelly, Mark (2007)
BACKGROUND: Individual differences in the regulation of affect are known to impact pain and other symptoms in rheumatoid arthritis. However, no studies have yet used a rigorous daily diary methodology to address the question of whether current pain is reduced when positive or negative affects are effectively regulated. PURPOSE: We used a prospective, repeated daily sampling design to infer the regulation of affect from day-to-day changes in affect intensity and examined how these changes in affect were prospectively related to pain from rheumatoid arthritis. METHOD: Ninety-four adult patients diagnosed with rheumatoid arthritis completed daily measures of pain and positive and negative affect over a period of 30 days. Information on demographic and disease status variables was collected during a medical evaluation. RESULTS: Results of hierarchical linear model analyses indicated that the regulation of both positive and negative affect from the prior day to the current day predicted significantly greater decreases in pain that day, resulting in up to a 28% reduction in pain intensity. These findings were partly influenced by disease status and demographic variables. CONCLUSION: This study suggests that the day-to-day regulation of negative and positive affect is a key variable for understanding the pain experience of individuals with rheumatoid arthritis and is a potentially important target for intervention.